Model Hubungan Peningkatan Kualitas Nilai Perusahaan Melalui Corporate Governance, Gender Direktur, Reputasi Audit Pada Perbankan Konvensional dan Perbankan Syariah di Indonesia Tahun 2013-2018 - Suharti Suharti; Anton Anton; Irawati Irawati (COSTING : Journal of Economic, Business and Accounting, 2020)
One important indicator factor for assessing the company's future prospects is to see the extent to which the company's profitability has grown. The purpose of this study was to determine the Relationship between Improving the Quality of Company Value through Corporate Governance, Gender Director, Audit Reputation in Conventional Banking and Islamic Banking in Indonesia 2013-2018. This research was conducted in listed companies that are members of the financial sector (Conventional and Sharia Banking) which are listed on the Indonesia Stock Exchange from 2013 to 2018 from 31 banking companies listed on the Indonesian stock exchange from a period of 6 years from 2013 to 2018. Methods used is purposive sampling, namely the technique of determining the sample with certain considerations. While the data analysis method using SEM and AMOS. The results of this study indicate that the Independent Board (Independent Board) does not have a significant positive effect on company performance and firm value (2) Gender Director (Female directorship) does not have a significant negative effect on company performance and firm value (3) Board Members (Managerial Board) ) has a significant positive effect on company performance; but Board Members (Managerial Board) do not have a significant positive effect on firm value. (4) Audit Reputation does not have a positive significant effect on company performance and firm value. Keywords: Audit Quality, Professional Accuracy, Competence, Ethics of Internal Auditors